Distribusi dan Pola Segregasi Karakter Kuantitatif F2 Persilangan Padi Situ Patenggang dengan IPB 3S - A A K Sudharmawan; IGP Muliarta Aryana; Jusmiati Jusmiati (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2019)
This study aims to determine the distribution and patterns of gene segregation that play a role in the inheritance of quantitative F2 traits resulting from the Situ Patenggang rice crossing with IPB 3S. The method used in this study is an experimental method carried out in July to December 2018 with a single plant cropping pattern. Data distribution was tested by Kolmogorov Smirnov test using SPSS 17.0 software and the suitability of segregation ratio using Chi-Square method with a real level of 5%. The results showed the nature of the number of productive puppies in normal distribution which means the character is controlled by many genes (polygenic). Plant height, number of empty grains and number of filled grains follow Mendel's segregation pattern with a ratio of 15: 1 (double dominant epistasis; controlled by two dominant genes that are both epistasis and regulate the same traits and can replace one another). the nature of the number of non-productive tillers, panicle length, and weight of 1000 grains does not follow the Mendel segregation ratio pattern or its modification for one trait and two traits is assumed because it is controlled by more than two genes (minor genes) so that their individual effects are difficult to distinguish.